Analysis of Capital and its Structure atthe Enterprises ofthe Oil and Gas Industry of Uzbekistan - Bekmukhamedova Malika Iskandarbekovna (Genius Journals, 2023)
This article discusses the terminology of capital and its structure. This facilitates the decision-making of manufacturing firms in Uzbekistan. The firm's capital structure consists of a specific combination of debt and equity issues to reduce potential pressure on its long-term funding. Many theories have been developed in the literature to explore such questions, and they tend to focus on what determinants might influence firms' decisions to leverage. In addition, the main determinants of capital structure in firms identified in various studies are tangibility, size, growth opportunities, profitability, and non-debt tax shields. In addition to this, issues such as corruption, the political climate, the nature of financial markets have also been identified as having a major impact on the capital structure of companies around the world. The article also highlights issues such as financial distress, threats of bankruptcy, solvency issues, and the risk of default due to an unstable economic and political situation, as possible dangers that may plague firms whose capital structure may be more inclined towards debt financing
Keywords: Determinants; Capital; Capital Structure